Assessment Of Predictive Value Of Serum Uric Acid Levels For Low Birth Weight In Pre-Eclampsia - Asma, Sadaf; Muntaha, Sidra Tul; Liaqat, Amerzish; Hassan, Farhan; Hayat, Sara; Ahmed, Rafiq (Journal of Rawalpindi Medical College, 2023)
OBJECTIVE: To assess the diagnostic accuracy of raised serum uric acid level in females with pre-eclampsia, in predicting low birth weight. SUBJESTS & METHODS: Cross sectional study carried out at Gynecology Department, FGSH Poly Clinic, Islamabad & duration of study was 6 months from July 21, 2021 to Jan 20, 2022. A total of 225 Preeclampsia pregnant female were clinically examined and included in the study. Blood sample were collected for serum uric acid and followed till the birth of the baby. RESULTS: The study included age ranged from 18 up to 40 years. Average age was 28.69years +5.01SD. Sensitivity & specificity of uric acid level in Serum in diagnosis of low birth weight are 85.71% and 81.42% respectively while it has positive predictive & negative predictive value of 51.43% & 96.13% respectively. Diagnostic accuracy of uric acid level in serum was 82.22%. CONCLUSION: Uric acid level in serum is of great diagnostic and prognostic importance in women with pre-eclampsia & helps in predicting low birth weight.